To the River's End : The High Country - Book 2 - Johnstone, William W.; Johnstone, J. A.; Johnstone, William W. (Thorndike, Maine : Center Point Large Print, 2025)
"Luke Ransom and Jug Sartain, trappers for the American Fur Company, made a formidable team when they partnered up in the grueling winter wilderness of Blackfoot Country. No hostile raids by man, no brutal obstacles of nature could stop them from snaring what they came for. The nicest surprise was that Luke came home with a wife--Willow, a lovely young Crow woman. Now, one year later, in this new trapping season of 1834, its Luke, Jug, and Willow who become the hunted . . . Theyre heading farther to the northwest in the mountain valleys of the Beaverhead and Pioneer Range. Its a known risk. The fearsome, kill-crazy Blackfoot claim exclusive rights to the territory--even the hardcase Hudson Bay trappers think twice about crossing that line. But its an unknown risk thats putting the lives of Luke, Jug, and Willow in danger. A kill-crazy, vengeance-seeking hound named Jake Purcell is following their every move. He aims to make a big killing in the High Country and take Willow alive for his own feral needs. A cold and bloody day in hell is storming on the horizon."--
Keywords: Trappers -- Fiction; Frontier and pioneer life -- Fiction; Revenge -- Fiction; Siksika Indians -- Fiction; Married people -- Fiction; Fur trade -- Fiction; West (U.S.) -- History -- To 1848; Fiction; Montana -- Fiction; Action and adventure fiction; Western fiction; Historical fiction; Large print books